Penerapan Teori Humanistik Carl Rogers Dalam Pembelajaran PAI - Prajoko, Indra; Abrori, M. Sayyidul (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2021)
This article aims to describe the humanistic theory of Carl Rogers, which is then formulated in the application of Islamic Education Learning. This study uses a library research method, namely by reviewing the literature related to research. The results of this study are focused on the attitudes of the human condition which include the ability to be self-aware, free to choose self-determination, freedom and responsibility anxiety as a basic element of seeking, personality development that arises based on the uniqueness of each individual. In therapy, this approach presents the conditions for maximizing self-awareness and development. This humanistic theory is suitable to be applied to learning materials that are personality formation, conscience, attitude change, and analysis of social phenomena. The indicator of the success of this application is that students feel excited, take initiative in learning, and there are changes in thought patterns, behavior, attitudes on their own accord. Students are expected to be human beings who are free, brave, not bound by the opinions of others, and manage their own personality responsibly without compromising the rights of others or violating applicable rules, norms, discipline, or ethics.